Fire safety in museum buildings: A case study of Perak Museum, Taiping, Malaysia - Salleh, Nurul Hamiruddin; Ahmad, A Ghafar (American Scientific Publishers, 2017)
In Malaysia, from 2001 to 2015 at least three museums have been involved in fires that destroyed the buildings and its contents. This is due to many factors such as insufficient fire safety systems, poor maintenance, and lack of fire safety awareness. In fact, the relevant authorities have also failed to provide sufficient guidance and good strategy in safeguarding the buildings that mostly gazetted as heritage buildings under the National Heritage Act 2005 (Act 645) from fire damages. The collection of primary data for this study was collected through on field observation as an approach to audit directly the practice of fire safety management in the heritage building. This study examines fire safety measures in the Perak Museum, a National Heritage building in Malaysia, with reference to the requirements of the Uniform Building By-Law (UBBL) 1984, the Fire Services Act 1988, the Occupational Safety and Health Act 1994 and four relevant Malaysian Standards that related to fire safety. The study discovers the studied building is relatively equipped with sufficient fire safety measures but the lack of proper fire safety management. The conflict between the security of contents and safety of people is also identified as a significant contribution of fire safety weaknesses in the building.